Commandos : The Inside Story of Britain's Most Elite Fighting Force - Parker, John, 1938- (London Bounty Printers, 2006)
Commando units of the Royal Marines engaged in virtually every military scenario involving British troops from 1945 to the present day. They became the elite of the British 'ready-to-go' forces, capable of deploying at a moment's notice to any trouble spot in the world. In this latest book in John Parker's acclaimed series on British military activity, dramatically recalled in their own words by men who were there, he recounts the major events in the 60-year history of British Commando forces..
Include Colour illustration and Index
Keywords: Commando troops -- Armed Forces--Commando troops -- Great Britain. Army -- Great Britain